EphA2 Expression Regulates Inflammation and Fibroproliferative Remodeling in Atherosclerosis. Issue 6 (8th August 2017) - Finney, Alexandra C.; Funk, Steven D.; Green, Jonette M.; Yurdagul, Arif; Rana, Mohammad Atif; Pistorius, Rebecca; Henry, Miriam; Yurochko, Andrew; Pattillo, Christopher B.; Traylor, James G.; Chen, Jin; Woolard, Matthew D.; et al.
Abstract : Background: Atherosclerotic plaque formation results from chronic inflammation and fibroproliferative remodeling in the vascular wall. We previously demonstrated that both human and mouse atherosclerotic plaques show elevated expression of EphA2, a guidance molecule involved in cell-cell interactions and tumorigenesis. Methods: Here, we assessed the role of EphA2 in atherosclerosis by deleting EphA2 in a mouse model of atherosclerosis (Apoe − /− ) and by assessing EphA2 function in multiple vascular cell culture models. After 8 to 16 weeks on a Western diet, male and female mice were assessed for atherosclerotic burden in the large vessels, and plasma lipid levels were analyzed. Results: Despite enhanced weight gain and plasma lipid levels compared with Apoe −/− controls, EphA2 −/− Apoe −/− knockout mice show diminished atherosclerotic plaque formation, characterized by reduced proinflammatory gene expression and plaque macrophage content. Although plaque macrophages express EphA2, EphA2 deletion does not affect macrophage phenotype, inflammatory responses, and lipid uptake, and bone marrow chimeras suggest that hematopoietic EphA2 deletion does not affect plaque formation. In contrast, endothelial EphA2 knockdown significantly reduces monocyte firm adhesion under flow. In addition, EphA2 −/− Apoe −/− mice show reduced progression to advanced atherosclerotic plaques with diminished smooth muscle and collagen content. Consistent with this phenotype, EphA2 shows enhanced expression after smooth muscle transition to a synthetic phenotype, and EphA2 depletion reduces smooth muscle proliferation, mitogenic signaling, and extracellular matrix deposition both in atherosclerotic plaques and in vascular smooth muscle cells in culture. Conclusions: Together, these data identify a novel role for EphA2 in atherosclerosis, regulating both plaque inflammation and progression to advanced atherosclerotic lesions. Cell culture studies suggest that endothelial EphA2 contributes to atherosclerotic inflammation by promoting monocyte firm adhesion, whereas smooth muscle EphA2 expression may regulate the progression to advanced atherosclerosis by regulating smooth muscle proliferation and extracellular matrix deposition. Abstract : Supplemental Digital Content is available in the text.